Developing a conceptual model of the factors forming divorce in the first five years of life: a grounded theory study - asghar abdollahi; hasan ahadi; Biuook Tajeri; Kobra HajiAlizadeh (مجله علوم روانشناختی, 2021)
Background: The available statistics show that the number of divorces registered in the early years of cohabitation, especially in the first five years, is higher than other years of marriage. Qualitative studies on the pathology of this issue and the development of a model to reduce its causative factors have been neglected. Aims: The aim of this study was to discover the antecedents and consequences of divorce in the first five years of married life and to develop a conceptual model of the contexts that shape it. Method: The study was conducted with a qualitative approach and data foundation method. The statistical population included all divorced couples in the first five years of living together in Tehran and Shiraz in 1398. 19 people were selected from the statistical population in a targeted manner. Participants were interviewed with in-depth semi-structured interviews, and the data were analyzed in accordance with the systematic approach of Strauss and Corbin in a regular and continuous process. Results: Finally, from the analysis and the conceptual model of the research, it can be concluded that divorce in the first years of family life is the result of individual, marital and family and socio-cultural weaknesses of the couple. Conclusions: Therefore, it is necessary for preventive programs in the field of community health to focus on education, skills training and reduction of individual and marital deficits for people about to get married and couples in the early years of married life.